2016
DOI: 10.4236/eng.2016.88047
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Compressive Strength of Baked Clay Cubes and Cylinders

Abstract: Reinforced Baked Clay (RBC) seems to be potential alternative of Reinforced Cement Concrete (RCC) for construction of low cost houses. In order to utilize RBC as a construction material for buildings, it is necessary to understand compression behaviour of baked clay. In this paper, relation between cube crushing strength and cylinder strength of baked clay is presented. For this purpose, clay beams were cast in a mould and compacted at a pressure of 6 MPa. The clay beams were dried and fired in a kiln at a tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Whereas the impact of incorporating different percentages of SF or MK on the hardened characteristics of FFACs cured at surrounding room temperature have been assessed in term of the compressive strength at 7, 14, 28, and 91 days, in addition to the 28 days flexural and splitting tensile strengths. Compression and splitting tensile strength tests were performed according to ASTM C39/C39M and ASTM C496/C96M, respectively (Figure 3d, and Figure 3e [22,23]. Three-point bending tests were applied in accordance to ASTM C1609/C1609 M. (Figure 3f) [24].…”
Section: Specimens Preparations and Testing Proceduresmentioning
confidence: 99%
“…Whereas the impact of incorporating different percentages of SF or MK on the hardened characteristics of FFACs cured at surrounding room temperature have been assessed in term of the compressive strength at 7, 14, 28, and 91 days, in addition to the 28 days flexural and splitting tensile strengths. Compression and splitting tensile strength tests were performed according to ASTM C39/C39M and ASTM C496/C96M, respectively (Figure 3d, and Figure 3e [22,23]. Three-point bending tests were applied in accordance to ASTM C1609/C1609 M. (Figure 3f) [24].…”
Section: Specimens Preparations and Testing Proceduresmentioning
confidence: 99%
“…The studies suggest that in addition to firing temperature [5][6][7][8][9], compression applied during casting of beams [10] plays an important role in increasing compressive strength of baked clay. The structural properties of RBC beams were investigated in terms of compressive strength [11], modulus of rupture [12], and load versus deflection response under static loading [13][14][15][16][17][18][19] and impact loading [20,21]. The problems of shrinkage and cracking of clay beams during dying [22] and firing process [23] are also addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous conducted studies reported that baked clay exhibited 1.5 to 2 times higher crushing strength than that of normal concrete [7][8][9][10][11][12][13][14][15]. RBC beams with tensile reinforcement, without shear and compressive reinforcement, only failed at the ultimate load of 80 kN applied at mid span [15].…”
Section: Introductionmentioning
confidence: 99%